2012
DOI: 10.3390/cryst2030893
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra of β″-Type BEDT-TTF Salts: Relationship between Conducting Property, Time-Averaged Site Charge and Inter-Molecular Distance

Abstract: Abstract:The relationship between the conducting behavior and the degree of charge fluctuation in the β″-type BEDT-TTF salts is reviewed from the standpoints of vibrational spectroscopy and crystal structure. A group of β″-type ET salts demonstrates the best model compounds for achieving the above relationship because the two-dimensional structure is simple and great diversity in conducting behavior is realized under ambient pressure. After describing the requirement for the model compound, the methodology for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…A similar infrared response, as to the anisotropy and the reflectance level, was recorded earlier for other metallic and superconducting β′′‐(BEDT‐TTF) 4 [A⋅M(C 2 O 4 ) 3 ]⋅Y materials 16. 48, 49 Our results can also be compared with the more anisotropic response of the β′′‐(BEDT‐TTF) 2 SF 5 CH 2 CF 2 SO 3 superconductor ( T c =5.2 K) 15. 47 The reflectance spectra of β′′‐2, β′′‐3 and α‐κ polarized in the low‐conducting interplane ∥c direction are flat with a rather low electronic background, as expected (Figure 1 (b)–(d)).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…A similar infrared response, as to the anisotropy and the reflectance level, was recorded earlier for other metallic and superconducting β′′‐(BEDT‐TTF) 4 [A⋅M(C 2 O 4 ) 3 ]⋅Y materials 16. 48, 49 Our results can also be compared with the more anisotropic response of the β′′‐(BEDT‐TTF) 2 SF 5 CH 2 CF 2 SO 3 superconductor ( T c =5.2 K) 15. 47 The reflectance spectra of β′′‐2, β′′‐3 and α‐κ polarized in the low‐conducting interplane ∥c direction are flat with a rather low electronic background, as expected (Figure 1 (b)–(d)).…”
Section: Resultssupporting
confidence: 76%
“…16 Of interest here are the β′′‐(BEDT‐TTF) 4 [(H 3 O)Fe(C 2 O 4 ) 3 ]⋅Y organic conductors. Recently, vibrational properties related to the CO fluctuating state have been reviewed by Yamamoto et al16, 48 for some β′′‐type salts including two organic metals, β′′‐(BEDT‐TTF) 4 [(H 3 O)Ga(C 2 O 4 ) 3 ]Pyridine and β′′‐(BEDT‐TTF) 4 [(H 3 O)Ga(C 2 O 4 ) 3 ]CH 2 Cl 2 , and superconducting β′′‐(BEDT‐TTF) 4 [(H 3 O)Ga(C 2 O 4 ) 3 ]PhNO 2 . It was shown that the conducting behavior in this class of materials is related to the time‐averaged molecular charges Δ ρ , defined as the charge difference between charge‐rich and charge‐poor donor molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in the β-and κ-type salts which are considered to have rigidly dimerized structure, the spin correlations coupled with charge fluctuations should be taken into account. 39 The Et 2 Me 2 Sb[Pd(dmit) 2 ] 2 with similar molecular arrangement with the present spin-liquid system shows charge-ordered ground states of which charge distributions are different between compounds.…”
Section: ç Magnetic Heat Capacity Coupled With Other Degrees Of Freedommentioning
confidence: 99%